Integrating Management Science into the HPC Research Ecosystem: How management science benefits from High Performance Computing. - Schryen, Guido (Communications of the ACM, 2020)
The author discusses his thoughts about the benefits of utilizing management science (MS) into high performance computing (HPC) research systems. The article define MS, examines the potential for HPC in solving MS problems, and gives examples including services developed by Bertelsmann Arvato Financial Solutions, the cloud-based software PathWise from Aon, and matching up algorithms in operations research.